2012
DOI: 10.1021/am301372d
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide for Catalytic Oxidation of Aqueous Organic Pollutants

Abstract: We discovered that chemically reduced graphene oxide, with an I(D)/I(G) >1.4 (defective to graphite) can effectively activate peroxymonosulfate (PMS) to produce active sulfate radicals. The produced sulfate radicals (SO(4)(•-)) are powerful oxidizing species with a high oxidative potential (2.5-3.1 vs 2.7 V of hydroxyl radicals), and can effectively decompose various aqueous contaminants. Graphene demonstrated a higher activity than several carbon allotropes, such as activated carbon (AC), graphite powder (GP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
284
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 680 publications
(292 citation statements)
references
References 44 publications
5
284
2
1
Order By: Relevance
“…It was worth noticing that the activation of persulfate by various carbonaceous materials, such as activated carbon [18], reduced graphene oxide (rGO) [19][20][21][22][23], carbon nanotubes (CNTs) [24][25][26][27][28], ordered mesoporous carbon (OMC) [29] and nanodiamond [30,31], had attracted much attention because of their environmental-friendly and high efficiency. Due to its high surface area, accessible mesopores and large pore volume, OMC had been applied in many areas such as adsorbents [32], catalysts and supports [33,34], and electrode materials [35].…”
Section: Introductionmentioning
confidence: 99%
“…It was worth noticing that the activation of persulfate by various carbonaceous materials, such as activated carbon [18], reduced graphene oxide (rGO) [19][20][21][22][23], carbon nanotubes (CNTs) [24][25][26][27][28], ordered mesoporous carbon (OMC) [29] and nanodiamond [30,31], had attracted much attention because of their environmental-friendly and high efficiency. Due to its high surface area, accessible mesopores and large pore volume, OMC had been applied in many areas such as adsorbents [32], catalysts and supports [33,34], and electrode materials [35].…”
Section: Introductionmentioning
confidence: 99%
“…They found that α-Mn2O3 cubic possessed the best catalytic activity and for 25 ppm phenol, 100% decomposition achieved within 60 min when catalyst usage of 0.4 g/L. Liang et al [15] reported mesoporous MnO2 supported Co3O4 nanoparticles synthesized by impregnation and their performances in heterogeneous activation of peroxymonosulfate (PMS) for phenol degradation. They found that when Co3O4 loading rate is 3 wt %, MnO2 supported Co3O4 catalysts could achieve 100% phenol removal at phenol concentration of 25 ppm within 120 min.…”
Section: Catalytic Oxidation Of Phenolmentioning
confidence: 99%
“…Cobalt oxides are proven to be the effective heterogeneous catalysts for PMS activation [12,13]. Nevertheless, due to the metal leaching, employment of cobalt based catalysts would result in the secondary pollution caused by the toxicity of cobalt ions [14,15]. Moreover, improper recycling of these nanosized particles would also bring contaminant to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the reduction GO could be used as catalysts in some organic reactions, such as hydrogenation of nitrobenzene and oxidation of organic pollutants, [35][36][37][38] for the zigzag edge, defects and surface area of reduction GO could act as catalytic active sites to facilitate the activation of reactant molecules. 35,36,39 Actually, because of the di®erent -electron structure and extra electronic state, the sp 2 carbon atoms in the presence of open edges were di®erent from that of located in a hexagonal cell as a -conjugated system for a basal plane in perfect graphene, 40 which made graphene nanoribbon very active for bonding with heteroatomic groups such as H, OH, CH 3 and halogen.…”
Section: Catalytic Properties Of R-go/ R-rgomentioning
confidence: 99%
“…35,36,39 Actually, because of the di®erent -electron structure and extra electronic state, the sp 2 carbon atoms in the presence of open edges were di®erent from that of located in a hexagonal cell as a -conjugated system for a basal plane in perfect graphene, 40 which made graphene nanoribbon very active for bonding with heteroatomic groups such as H, OH, CH 3 and halogen. 41 Therefore, the unique electronic structure of zigzag edges and defects on the R-GO/or R-RGO, to their high active catalyst for 4-NP.…”
Section: Catalytic Properties Of R-go/ R-rgomentioning
confidence: 99%